Gender-based violence. A current vision - Figueroa Gutarra, Edwin (2019)
The issues of gender-based violence represent a concern in all contemporary legal systems, and the examination of their causes and manifestations is a pending task for the regional human rights protection systems. It remains to be elucidated, in this context, the problem of visibility of gender-based violence and what is the role of society as a whole with respect to this phenomenon.